Determinants of Circular Economy-Based Household Waste Management Effectiveness in Community 3R Facilities - Muhamad Padli; Ida Bagus Made Agung Dwijatenaya; Musmuliadi Musmuliadi (Indonesian Journal of Business and Entrepreneurship Research, 2026)
This study examines the determinants of the effectiveness of a circular economy-based household waste management program in community 3R facilities. Specifically, it analyzes the partial and simultaneous effects of waste reduction at source, reuse of used goods, recycling into new products, community participation in waste management, and the economic value of waste management outputs on program effectiveness. The study employed a quantitative approach with inferential statistical analysis. From a population of 5,133, a sample of 98 respondents was determined using the Slovin formula. Primary and secondary data were collected through questionnaires and interviews, and the data were analyzed using multiple regression with SPSS. The instrument testing results confirmed that the research measures were valid and reliable. The findings show that waste reduction at source has a positive and significant effect on program effectiveness. The economic value generated from waste management outputs also has a positive and significant effect on program effectiveness. Simultaneously, all independent variables have a significant effect on the effectiveness of the household waste management program. These findings indicate that circular economy-based waste management is more effective when reduction practices are strengthened at the household level and when waste processing generates tangible economic value. The study highlights the importance of policy support, community behavioral change, and the development of waste-based economic activities to improve the performance of community waste management programs.